UMPSA launches Sustainable Practice Carbon Free Electric Vehicles - Mimi Rabita, Abd Wahit (UMPSA, 2023)
PUTRAJAYA, 23 October 2023 - In line with the National Green Agenda, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) launched the use of electric vehicles in utilising technology and innovation for the betterment of future generations.